Protesting sex slavery : the textile doll as activism : an exegesis presented in partial fulfilment of Master of Fine Arts, Massey University, Wellington - White, Rosie (Massey University, 2017)
Natural disasters, climate change, war and poverty have increased the vulnerability of migrants to modern slavery. Human traffickers prey upon post-disaster migrant populations who are vulnerable to promises of jobs and security. And among the most vulnerable are children, who are often given no choices. The incredibly sad yet lucrative side of sex trafficking is that a child or a young person’s body can be sold repeatedly for high profit with low overheads – often leading to a lifetime of severe trauma. This project involves the textile practice of cloth dolls. Dolls have rich cultural significance. They are used in children’s play, religious ceremonies, and are often dressed in national costumes. They are used in counselling to help victims deal with traumatic experiences. And as artist Eric Fischl (Fischl 2015) points out, they are a widespread genre in contemporary art, used by artists such as Hans Belmar, Cindy Sherman, Louise Bourgeois, and Morten Bartlett. And textiles themselves have been used as a form of protest from suffragette banners to the dolls of the Chilean Arpilleras. The cloth dolls that have been made as part of this project highlight and protest issues of sex trafficking. The dolls are darned and patched, just as the women and children, who are rescued by organisations that fight against modern slavery, need mending and restoration. They have a name tag on their ankles with a URL directing people to an agency that fights modern slavery and its consequences. They have been left in public places and displayed in a gallery setting.
Keywords: Rosie White; Criticism and interpretation; Dolls in art; Social aspects; Human trafficking; Art and society; Art and social action; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art